“A mulher toma um pilgie e vai trabalhá”: uma etnografia com colonas do leite em Santo Cristo- RS - Froelich, Patrícia Rejane (2022)
In this thesis I seek to understand the meanings that rural women in Santo Cristo-RS confer to work, body and health through a pandemic ethnography (methodology adapted for the pandemic period of Covid-19), with data collection in 2020 and analytical maturation until mid-2022. The theoretical framework is based on anthropology, sociology, and rural extension. Besides the aforementioned triad, the text is also studded with the anguishes of academic production and writing in a period of health crisis and limited financial resources. The proposal that anchors all the creative energy mobilized here aims to promote epistemological and social reflections, as well as fruitful interludes in the debate on contemporary ruralities. I have privileged writing in the female gender to question the hegemonic pattern and to sponsor new molds of decolonial science. Many questions adjacent to the research problem present themselves throughout the text to temper rumination: what is it to be a rural woman in the context of dairy cattle farming in northwestern Rio Grande do Sul? What is it like to reflect on oneself in a context of physical exhaustion? What are the psycho-emotional impacts of the pandemic for them/us? What is the importance of research in a period of scourges? The research, and consequently the writing, went through particular affectations, tuned to the grope of understanding the way of being a rural woman, epicentered in a locality of the northwest of Rio Grande do Sul and how this is related to broader social issues (of health and work). Although the notions of body, health, and work have been developed in separate chapters, their intertwining and cultural consonance is remarkable. A body fit for work means health for the women surveyed, therefore, a moral value is given to this resourcefulness. Family is commonly rated as the most important thing in their lives. Most of them declared to be happy with their routine, even though they aspire to a less expensive profession for their offspring.